TEAM STEALTH F-117 - Jolly, Randy; Shelton, Robert (Airlife Publishing Ltd., 1993)
Over 100 exciting photos, many never-before-published, featuring the "premier star" of Desert Storm - the F-117A stealth fighter. Dramatic air-to-air photos as well as detailed photos of the aircraft on the ground and in Saudi make "Team Stealth" as insightful and detailed picture history of the F-117A's recent activities